COACHEN, LEHREN UND LERNEN MIT MUSIK;PRAXISLEITFADEN FUR SCHULE UND HOCHSCHULE, ERWACHSENENBILDUNG UND LEBENSLANGES LERNEN - HANS-JURGEN BOMEYER;GERNOT BRAUER;CLIVE F. W. FLYN (VERLAG BARBARA BUDRICH, 2020)
Make use of the power of music, help people to learn with more engagement and success and make intellect and emotion vibrate together! Examples from the fields of business, adult training and school prove how amazingly better people absorb and retain knowledge and messages when they are put into sound. In this volume the experienced trainer Hans-Jürgen Boßmeyer reports how much joy and learning success listeners can have with this kind of knowledge transfer. The book informs about how one can use the power of music to coach people more successfully and let them learn with more commitment and greater success. The volume offers a multitude of practical examples and applications from the fields of school and university, vocational training, adult education and integration work.Teaching, learning and coaching with music is a proven method to use music as a motivator. It opens our senses, appeals to us and allows us to establish a new relationship to the texts we set to music.